2023
DOI: 10.3390/healthcare11091253
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Reference Data for Fitness Assessment of Law Enforcement Officers Using a Qualitative Systematic Review

Abstract: Physical fitness tests are a standard means of evaluating the competence of police officers. This qualitative review aims (i) to document, compare, and examine the reference values available in the current literature regarding fitness tests for Law Enforcement Officers (LEOs), and (ii) to define reference values for the most used fitness tests to assess and predict police officer performance. A total of 1879 records were collected for review from two major literature databases, PubMed and ScienceDirect. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Although several studies show that there is evidence of a decrease in muscle strength exercises with age, others state that there is no significant difference in women across age groups [ 22 , 31 ]. In accordance, the difference in the performance of the different tests can be attributed to several factors, such as (i) the level of physical condition; (ii) the type of training performed; and (iii) cultural or social factors that influence the level of physical activity [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies show that there is evidence of a decrease in muscle strength exercises with age, others state that there is no significant difference in women across age groups [ 22 , 31 ]. In accordance, the difference in the performance of the different tests can be attributed to several factors, such as (i) the level of physical condition; (ii) the type of training performed; and (iii) cultural or social factors that influence the level of physical activity [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining physical fitness (PF) is essential to efficiently face the demands of this profession, as it is considered critical to adequately perform the activities associated with their role [ 1 ]. In this context, the literature highlights body composition, cardiorespiratory fitness, strength, muscular endurance, flexibility, agility, and speed as relevant attributes for the performance of the police profession [ 2 , 3 , 4 , 5 ], as well as a guarantee of health and well-being [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature (see [29,30]) showed that a variety of physical fitness tests exist to assess and predict police officer performance, and the most applied fitness assessments were (i) push-ups, sit-ups, vertical jump, and handgrip tests for muscle strength; (ii) 12-min Cooper, 1.5-mile run, 2.4-mile run, and 20 m shuttle run for aerobic capacity; and (iii) sit-and-reach for flexibility. According to Massuça et al [29], more and more tests are being used to assess various fitness attributes, such as muscular strength and aerobic capacity.…”
Section: Introductionmentioning
confidence: 99%